2022
DOI: 10.3389/fneur.2022.919596
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor, vestibular, reaction time, and cognitive tests as objective measures of neural deficits in patients post COVID-19 infection

Abstract: ObjectiveAn alarming proportion (>30%) of patients affected by SARS-CoV-2 (COVID-19) continue to experience neurological symptoms, including headache, dizziness, smell and/or taste abnormalities, and impaired consciousness (brain fog), after recovery from the acute infection. These symptoms are self-reported and vary from patient to patient, making it difficult to accurately diagnose and initiate a proper treatment course. Objective measures to identify and quantify neural deficits underlying the sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…One of the earliest studies on post-COVID cognitive deficit suggested a substantial impairment in response speed in acute or sub-acute stage of COVID-19, 6 while one investigation reported a modest deficiency only in severe or cognitive cases, 12 and another online study reported no deficit in response speed in infected individuals with cognitive symptoms. 30 In addition, Martin et al found a deficit in perceptual processings speed in PCC patients with cognitive complaints. 10…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest studies on post-COVID cognitive deficit suggested a substantial impairment in response speed in acute or sub-acute stage of COVID-19, 6 while one investigation reported a modest deficiency only in severe or cognitive cases, 12 and another online study reported no deficit in response speed in infected individuals with cognitive symptoms. 30 In addition, Martin et al found a deficit in perceptual processings speed in PCC patients with cognitive complaints. 10…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest studies on post-COVID cognitive deficit suggested a substantial impairment in response speed in the acute or sub-acute stage of COVID-19, 6 while one investigation reported a modest deficiency only in severe or cognitive cases, 12 and another online study reported no deficit in response speed in infected individuals with cognitive symptoms. 30 In addition, Martin et al. found a persistent deficit in perceptual processing speed in patients with PCC with cognitive complaints.…”
Section: Discussionmentioning
confidence: 99%